Low-Paid Employment and Unemployment Dynamics in Australia - Lee, W; Wooden, M; Buddelmeyer, H (My University, 2009)
This paper uses longitudinal data from the Household, Income and Labour Dynamics in Australia (or HILDA) Survey to examine the extent to which the relatively high rates of transition from low-paid employment into unemployment are the result of disadvantageous personal characteristics or are instead a function of low-paid work itself. Dynamic random effects probit models of the likelihood of unemployment are estimated. After controlling for unobserved heterogeneity and initial conditions, we find that, relative to high-paid employment, low-paid employment is associated with a higher risk of unemployment, but this effect is only significant among women. We also find only weak evidence that low-wage employment is a conduit for repeat unemployment.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Finance; Employment; Finance -- Income (Salary and Wages); Income, wealth and finances; Labour market; Finance; Employment; Income (Salary and Wages); Employment and unemployment; Income, wealth and finances